Protective water layer in a plasma mini-reactor revealed by the composition of the exhaust gas. (5th March 2019) - Lemont, F.; Rousset, F.; Marchand, M.; Russello, A.
Highlights: An indirect technique to measure plasma reactor temperatures is presented. The CO/CO2 molar ratio is shown to be an accurate proxy. Comparing measured and calculated values reveals incomplete water vaporisation. The non-vaporized portion forms a protective sleeve in the outlet nozzle. Abstract: Plasma mini-reactor development is at the heart of research conducted to miniaturize thermal processes for the treatment of hazardous liquids. Their optimization requires an understanding of the physicochemical phenomena that take place there, the observation of which is complicated by the extreme temperature levels. The work described in this study shows that a modeling of the energy flows exchanged in a mini-reactor in which water is injected to control temperature leads to inconsistent results when compared with the measurement of the CO/CO2 ratio at the outlet of the nozzle. Indeed, the temperature calculation versus the CO/CO2 ratio by a modeling of the thermodynamic equilibria achieved in complex chemical systems reveals significant differences that can be explained by a partial vaporization of the injected water due to a very high gas velocity. This result highlights that the rest of the non-evaporated water forms a water layer on the internal walls of the reactor what verified by a direct measurement of the temperature closest to the inner wall of the mini-reactor. The presence of this water layer explains why the thermo-oxidation of an aqueous solution injected into a plasma is much less effective than the photo-oxidation induced by the UV radiation it emits. Furthermore, the presence of this layer could explain why the level of corrosion remains very low after the combustion of various organic liquids loaded with chlorine, sulphur or phosphorus. This opens wide perspectives on the development of reactor operating in extreme physicochemical environments.